(untitled) (Journal of Hama University, 2024)
The aim of this research is to demonstrate the effectiveness of using the Bayes statistical technique in selecting the components of the optimal investment portfolios, by using the James-Stein model in the portfolio selection process, by applying it to a sample of the shares of companies listed in the Damascus Stock Exchange during the period(20/2/2019-20/3/2023), and to achieve this goal, the expected returns from each share and the associated risk levels were calculated, based on the techniques of the (mean-varianc) model, based on the fact that it is the basis that will be re-estimated within the framework of the James-Stein model and then used In the process of selecting the components of the investment portfolios, and after re-estimating each of the expected returns and the covariance matrix, the selection process was started and the components of the stock portfolios were determined by finding the weights of the components of each of them, and then the expected returns from the portfolios and the accompanying degrees of risk up to to design the efficient limit curve By comparing the characteristics of the portfolios resulting from the application, it is clear how effective the use of Bayes statistical technique is in the examples of investment portfolios. Despite its modification of the mechanism of the estimation process, its practical procedures do not include any steps that limit the tendency of capital concentration and the irrational selection and exclusion of the components, in addition to not taking into account the different patterns of investors and their inclinations towards risk.